Labor Violence in the Emergency Room in times of COVID-19: perceptions of the nursing team (Research, Society and Development, 2022)
The objective was to know the perceptions of the nursing staff about workplace violence and its possible intensification in times of COVID-19 confrontation in the hospital emergency unit. This is a qualitative study, carried out with 14 professionals Nurses and Nursing Technicians of the Emergency Room of a university hospital in the north of the State of Paraná. Individual, semi-structured, audio-recorded interviews were carried out, fully transcribed and submitted to content analysis. The questions focused on understanding the employees' views about workplace violence concerning its concept, the daily life of the front line in confronting COVID-19, the triggering factors in the urgency and emergency unit, and suggestions for strengthening safety in the Emergency Room. Five categories of analysis emerged: “The meaning of workplace violence and the face of the aggressors”; “Labour violence in the emercency sector reference for COVID-19”; “The triggering factors of labor violence in the Emercency Room”; “Episodes of workplace violence for victims”; and “Professionals suggestions for coping with workplace violence”. It was found that workplace violence is a multifaceted reality and portrays a great challenge to be overcome by the nursing team. Furthermore, with the emergence of COVID-19, there was a change in the profile of clients, intensifying the occurrence of workplace violence.